2012
DOI: 10.1111/j.1574-6968.2012.02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential deletion of all the polyketide synthase and nonribosomal peptide synthetase biosynthetic gene clusters and a 900-kb subtelomeric sequence of the linear chromosome of Streptomyces coelicolor

Abstract: Streptomyces coelicolor, with its 8 667 507-bp linear chromosome, is the genetically most studied Streptomyces species and is an excellent model for studying antibiotic production and cell differentiation. Here, we report construction of S. coelicolor derivatives containing sequential deletions of all the 10 polyketide synthase (PKS) and nonribosomal peptide synthetase (NRPS) biosynthetic gene clusters and a 900-kb subtelomeric sequence (total c. 1.22 Mb, 14% of the genome). No obvious differences in growth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 34 publications
2
46
0
1
Order By: Relevance
“…Strain ZM12 was derived from S. coelicolor , probably the best-studied model Streptomyces , through deleting all ten native PKS and NRPS gene clusters present in its genome. [16] HPLC showed that this strain produced very few metabolites (Figure S2A). However, upon introducing pSETHSAF3, both compounds 2 and 3 were produced as the main metabolites in strain ZM12, in addition to a number of minor peaks.…”
mentioning
confidence: 99%
“…Strain ZM12 was derived from S. coelicolor , probably the best-studied model Streptomyces , through deleting all ten native PKS and NRPS gene clusters present in its genome. [16] HPLC showed that this strain produced very few metabolites (Figure S2A). However, upon introducing pSETHSAF3, both compounds 2 and 3 were produced as the main metabolites in strain ZM12, in addition to a number of minor peaks.…”
mentioning
confidence: 99%
“…PCR-targeted gene replacement procedure of Gust et al (2003) is also very useful for generating large deletions of chromosomal segments, including ten secondary metabolite biosynthetic gene clusters from S. coelicolor chromosome (Zhou et al 2012). The targeted recombination strategy adds an alternative approach for genome shuffling in Streptomyces genomes.…”
Section: Application For Identification Of Essential Regions and Genomentioning
confidence: 99%
“…Later, the construction of S. coelicolor derivatives containing sequential deletions of all the 10 PKS and NRPS biosynthetic gene clusters and a 900-kb subtelomeric sequence (total ca. 1.22 Mb, 14% of the genome) was performed to generate a further minimized S. coelicolor strain 43 . Recently, the CRISPR-Cas system has emerged as a popular tool for genome editing 44, 45 .…”
Section: Host Engineering: Minimized Genomes and Engineered Hostsmentioning
confidence: 99%